Continuous Molecular Evolution of Protein-Domain Structures by Single Amino Acid Changes - Meier, Sebastian; Holstein, Thomas W.; Özbek, Suat (Current biology, 2007)
Summary Protein structures cluster into families of folds that can result from extremely different amino acid sequences [1]. Because the enormous amount of genetic information generates a limited number of protein folds [2], a particular domain structure often assumes numerous functions. How new protein structures and new functions evolve under these limitations remains elusive. Molecular evolution may be driven by the ability of biomacromolecules to adopt multiple conformations as a bridge between different folds [3-6]. This could allow proteins to explore new structures and new tasks while part of the structural ensemble retains the initial conformation and function as a safeguard [7]. Here we show that a global structural switch can arise from single amino acid changes in cysteine-rich domains (CRD) of cnidarian nematocyst proteins. The ability of these CRDs to form two structures with different disulfide patterns from an identical cysteine pattern is distinctive [8]. By applying a structure-based mutagenesis approach, we demonstrate that a cysteine-rich domain can interconvert between two natively occurring domain structures via a bridge state containing both structures. Comparing cnidarian CRD sequences leads us to believe that the mutations we introduced to stabilize each structure reflect the birth of new protein folds in evolution.